Study guide [for] The humanities : cultural roots and continuities . V.1 : Three cultural roots - .; Brown, Charlotte Vestal; Dunbar, Roberta Ann.; Witt, Mary Ann Frese (Boston : Houghton Mifflin, 1997)
Earliest civilizations. The greco-Roman and Judeo-Christian roots. Medieval cultures.
Keywords: Civilization; Western civilization; Civilization, Western -- History; Civilization, Western -- History -- Sources; Humanities; Africa -- Civilization; Africa -- Civilization -- Sources